Linguistic features of literary theme: some halliday-type principles applied to surfacing (Margaret Atwood 1972) - M. Nélia Scott (Ilha do Desterro)
Halliday divides the functions of language into three macro-functions' which he calls: ideational function, expressing content, or the propositional content of the speaker's xperiences of the real and inner world; interpersonal function, which is the means whereby we achieve communication, taking on speech roles vis-à-vis other people, complaining, narrating, enquiring, encouraging, etc.; and textual function, which serves to connect discourse, weaving it together. Under this latter function comes the notion of cohesion. Phoric' elements are parts of the reference system needed for a text to be cohesive. We elucidate and refer to 'phoric' elements in more detail below. It is important to note that all these three macro-functions are present at the same time in a text.